Exploring the Factors Affecting the Student's Acceptance of Using IAIN Ponorogo E-Learning through the UTAUT Model - Nabila, Rahma; Priyanto, Priyanto; Shiddiq, Jamaluddin (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
This study aims to analyze the factors affecting the student's acceptance of e-learning IAIN Ponorogo through the UTAUT model, which consists of four primary constructs: performance expectancy, effort expectancy, social influences, and facilitating conditions. Those constructs are influenced strongly by moderating variables, which include age, gender, experience, and volunteerism of use. This model will be used to analyze the e-learning system of IAIN Ponorogo based on LMS Moodle version 1.9.15 with slight modifications. The research type is quantitative-explanative research. The subjects are students of IAIN Ponorogo, with 400 respondents as a sample from a total population of 8112 students using a stratified random sampling technique. Data was collected from the results of a closed questionnaire and analyzed by the Partial Least Square (PLS) method with WarpPLS software, which consists of three steps: the design of the inner model, the outer model, and the evaluation of the model. The findings indicated that: (1) Facilitating condition factors have a positive and insignificant effect on students' behavior with a parameter coefficient value of 0.7% and a p-value greater than 5%; (2) The interest in use factor has a positive and significant effect on the use behavior of students with a parameter coefficient value of 0.735 and a p-value greater than 5%.